Função pulmonar de crianças com leucemia aguda - Macedo, Thalita Medeiros Fernandes de (2012)
Introduction: The leukemias are the most common malignancy in children and adolescents. With the improvement in outcomes, there is a need to consider the morbidity to generate the protocols used in children under treatment. Aim: To evaluate pulmonary function in children with acute leukemia. Method: This study is an observational cross sectional. We evaluated 34 children distributed in groups A and B. Group A comprised 17 children with acute leukemia in the maintenance phase of chemotherapy treatment and group B with 17 healthy students from the public in the city of Natal / RN, matched for gender, age and height. The thoracic mobility was evaluated by thoracic expansion in the axillary and xiphoid levels. Spirometry was measured using a spirometer Microloop Viasys ® following the rules of the ATS and ERS. Maximal respiratory pressures were measured with digital manometer MVD300 (Globalmed ®). The maximal inspiratory pressure (MIP) and maximal expiratory pressure (MEP) were measured from residual volume and total lung capacity, respectively. The data were analyzed using the SPSS 17.0 software assigning the significance level of 5%. Descriptive analysis was expressed as mean and standard deviation. T'student test was used to compare unpaired values found in group A with group B values, as well as with the reference values used. To compare the respiratory coefficients in the axillary level with the xiphoid in each group, we used paired testing t student. Results: Group A was significantly decreased thoracic mobility and MIP compared to group B, and MIP compared to baseline. There was no significant difference between spirometric data from both groups and the values of group A with the reference values Mallozi (1995). There was no significant difference between the MIP and MEP values and lower limits of reference proposed by Borja (2011). Conclusion: Children with acute leukemia, myeloid or lymphoid, during maintenance phase of chemotherapy treatment have reduced thoracic mobility and MIP. However, to date, completion of clinical treatment, the spirometric variables and the strength of the expiratory muscles appear to remain preserved in children between five and ten years